Quantifying the work demands of municipal waste workers to determine physical workload and perception - Mamabolo, Lerato (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics)
Objective: This study aimed to quantify physical and perceptual workloads through the nature of the work demands of municipal waste workers. Waste workers investigated were waste collectors, street sweepers [or public cleansers], drivers and mechanics. Methods: 154 City of Tshwane municipal waste workers volunteered to participate in the study. Observation-based tools were used to measure physical workload namely, the RAMP 1 and 2, REBA and RULA, and the hand-held dynamometer was used for pushing and pulling tasks. Subjective perceptual questionnaires were used to measure Perceptual load namely the NASA TLX and the QWIQ. Results: Differences in physical workload were evident between the occupation groups. Round bin collection was the waste collection type pertaining to the highest work-related risk of musculoskeletal development. Public cleansers and flatbed truck collectors' results displayed lower task-related risks associated in relation to the other occupations. Significant differences were found between the groups, particularly between waste collectors and drivers [had high workload outputs] in relation to public cleansers [low workload] for both perceptual workload tools. A significant difference was found in the mental and physical demands, as well as the organisational constraints and quantitative workloads. Mechanics showed no significant differences between groups but had high levels of frustration. Conclusion: A relationship between physical and perceived workload intensity is evident. development of musculoskeletal diseases and injury shall incur if measures are not reinstated.
Keywords: Refuse collectors -- South Africa City of Tshwane Metropolitan Municipality; Manual work -- South Africa City of Tshwane Metropolitan Municipality; Human engineering; Risk assessment; Work capacity evaluation; Mental fatigue